2021
DOI: 10.3390/ijms22094351
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Light Chains in Cardiac Development and Disease

Abstract: The role of regulatory light chains (RLCs) in cardiac muscle function has been elucidated progressively over the past decade. The RLCs are among the earliest expressed markers during cardiogenesis and persist through adulthood. Failing hearts have shown reduced RLC phosphorylation levels and that restoring baseline levels of RLC phosphorylation is necessary for generating optimal force of muscle contraction. The signalling mechanisms triggering changes in RLC phosphorylation levels during disease progression r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 125 publications
(167 reference statements)
1
17
0
Order By: Relevance
“…These functional changes correlated with decreased RLC phosphorylation, increased cTnT phosphorylation, and increased cMyBP-C phosphorylation at Ser302 (Figures 3, 4). It was previously suggested that RLC phosphorylation is affected by aging (Markandran et al, 2021). Despite, there are no statistical differences in RLC phosphorylation between aged WT vs. aged KO mice (Figures 3A,B,H); there is a trend of decreased phosphorylation in the aged KO mice group (p = 0.07) suggesting that the deletion of β-arrestin-2 in aged mice, besides aging, contributes even more to decreased levels in RLC phosphorylation.…”
Section: Discussionmentioning
confidence: 71%
“…These functional changes correlated with decreased RLC phosphorylation, increased cTnT phosphorylation, and increased cMyBP-C phosphorylation at Ser302 (Figures 3, 4). It was previously suggested that RLC phosphorylation is affected by aging (Markandran et al, 2021). Despite, there are no statistical differences in RLC phosphorylation between aged WT vs. aged KO mice (Figures 3A,B,H); there is a trend of decreased phosphorylation in the aged KO mice group (p = 0.07) suggesting that the deletion of β-arrestin-2 in aged mice, besides aging, contributes even more to decreased levels in RLC phosphorylation.…”
Section: Discussionmentioning
confidence: 71%
“…Some of the mutations disrupt phosphorylation sites of the myosin regulatory light chains that is proposed to be mediated by Ca 2+ /calmodulin-dependent protein kinase and essential for muscle contraction. 28 Mutations in myosin-binding protein C also leads to hypertrophy 29 and decreased desmin expression levels associated with the progression of heart failure. 30 Imaging studies demonstrate reduced contractility in the atria of people with severe obesity, with remodeling and improved contractility following weight loss interventions.…”
Section: Clinical Importancementioning
confidence: 99%
“…RLC phosphorylation facilitates force production by increasing the maximal isometric tension, calcium sensitivity of force and rate of force redevelopment at intermediate and maximal calcium activation levels [ 16 , 17 ], and also enhances the motility of human beta-myosin under load as seen by in vitro motility assays [ 18 ]. The levels of RLC phosphorylation decreased in end-stage HF of both human and animals [ 19 ]. However, it is not known whether the changes in RLC phosphorylation drive the functional changes during HF progression, or vice versa.…”
Section: Introductionmentioning
confidence: 99%